Integrasi Pasar Modal ASEAN – 5 Pra dan Pasca Pandemi - Setyoadi Pambudi, Setyoadi Pambudi (Universitas Nahdlatul Ulama Blitar, 2023)
The capital market is one of the main indicators for the success of a country's economic growth. Because the Capital Market will have a big positive impact with the flow of funds coming in through both domestic and foreign investors. So to see how good or bad the capital market in a country is, you can look at the country's capital market index. The purpose of this study is to describe the correlation of the main exchanges in Asia and the United States to the JCI, the correlation of the highest and lowest exchanges on the main ASEAN-5 exchanges, the linkages of the main ASEAN-5 exchanges. The analytical tool used is a simple correlation with monthly data for 2015 – 2021 on the main ASEAN-5 exchanges. The correlation results show that the main capital markets in ASEAN-5 are classified as low-strong. With the lowest value of 0.167 and the highest of 0.738. The conclusion from the results of this study is that the main exchange correlations in ASEAN-5 are integrated.